The invaded range of the tree fern Sphaeropteris cooperi is predicted to shrink in two southern hemisphere biodiversity hotspots - (:unkn) unknown (My University, 2025)
Source Agritrop Cirad (https://agritrop.cirad.fr/613788/) * Autres projets (id;sigle;titre): ;;(FRA) Oil BodiEs for INNovative food products: from plant seed processing to digestive fate//
Keywords: African Research